Operational characteristics of oscillating heat pipe at sub-zero temperature for cold energy storage - Im, Yong Hoon; Lee, Ju Young; Ahn, Tae In; Youn, Young Jik (Pergamon Press Ltd., 2023)
This study first suggested a natural cold energy storage based on oscillating heat pipe (OHP) and pre-sented the experimental investigation on the operational characteristics of the OHP at sub-zero tempera-tures for cold energy production. In the present experiment, the OHP was manufactured using a copper meandering tube with inner diameter of 2 mm and 5-turns, and R-134a was used as the working fluid. The manufactured OHP-based cold energy storage module was put into the temperature-controlled cool-ing chamber and the cold energy storage performance was evaluated at various low ambient temperature conditions. The thermal resistance of the OHP had a minimum value of 0.18-0.23 K/W regardless of the ambient temperature change. However, the lower ambient temperature caused significant thermal resis-tance decrease at water-ice temperature of 0 degrees C and the minimum thermal resistance was 1.18 K/W at the lowest ambient temperature of-20 degrees C. When the cold energy was stored in the final form of ice, the present OHP module could store the total maximum amount of cold heat of 2,784 kJ, consisting of sensible heat of 662 kJ and latent heat of 2,345 kJ at the lowest ambient temperature of-20 degrees C. It was concluded that the lower ambient temperature causes the stable and higher thermal performance of the OHP which increases the amount of stored cold heat by sensible heat and makes the OHP module possi-ble to produce the cold heat more quickly.(c) 2022 Elsevier Ltd. All rights reserved.